2021
DOI: 10.3390/jcm10030553
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Intake and Alcohol–SNP Interactions Associated with Prostate Cancer Aggressiveness

Abstract: Excessive alcohol intake is a well-known modifiable risk factor for many cancers. It is still unclear whether genetic variants or single nucleotide polymorphisms (SNPs) can modify alcohol intake’s impact on prostate cancer (PCa) aggressiveness. The objective is to test the alcohol–SNP interactions of the 7501 SNPs in the four pathways (angiogenesis, mitochondria, miRNA, and androgen metabolism-related pathways) associated with PCa aggressiveness. We evaluated the impacts of three excessive alcohol intake behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 72 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…The authors of this manuscript concluded: "Reducing alcohol consumption could slow prostate cancer disease progression." Another study of 3306 PCa patients with European ancestry from the PCa Consortium aimed to examine alcohol intake and SNPs in the four pathways associated with PCa aggressiveness (angiogenesis, mitochondria, miRNA, and androgen metabolism-related pathways) [131]. Investigators found that excessive alcohol intake significantly impacts PCa aggressiveness within the following genetic subgroups: CAMK2D (calcium/calmodulin-dependent protein kinase II delta, enriched in the cell cycle and the calcium signaling pathway), PRKCA (protein kinase C alpha, the modulator of cell adhesion and transformation), and ROBO1 (roundabout guidance receptor 1, cell migration factor and a tumor suppressor gene).…”
Section: The Impact Of Alcohol On the Aggressiveness Of Prostate Tumo...mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of this manuscript concluded: "Reducing alcohol consumption could slow prostate cancer disease progression." Another study of 3306 PCa patients with European ancestry from the PCa Consortium aimed to examine alcohol intake and SNPs in the four pathways associated with PCa aggressiveness (angiogenesis, mitochondria, miRNA, and androgen metabolism-related pathways) [131]. Investigators found that excessive alcohol intake significantly impacts PCa aggressiveness within the following genetic subgroups: CAMK2D (calcium/calmodulin-dependent protein kinase II delta, enriched in the cell cycle and the calcium signaling pathway), PRKCA (protein kinase C alpha, the modulator of cell adhesion and transformation), and ROBO1 (roundabout guidance receptor 1, cell migration factor and a tumor suppressor gene).…”
Section: The Impact Of Alcohol On the Aggressiveness Of Prostate Tumo...mentioning
confidence: 99%
“…In addition, the authors observed an additional moderate link between alcohol and SNPs of genes associated with PCa aggressiveness. These are HGF (hepatocyte growth factor), PDGFB (platelet-derived growth factor subunit B), SYK (spleen-associated tyrosine kinase), PDGFD (platelet-derived growth factor D), and COL4A3 (collagen type IV alpha 3 chain) [131].…”
Section: The Impact Of Alcohol On the Aggressiveness Of Prostate Tumo...mentioning
confidence: 99%
“…Studies have shown that alcohol consumption is linked to many diseases, including alcohol dependence, cardiovascular and cerebrovascular diseases, digestive system diseases, and [7]. For example, SNPs on the CAMK2D, ROBO1, and PRKCA genes, may increase an individual's vulnerability to excessive alcohol intake and the development of aggressive prostate cancer [8]. And the GA and AA genotypes on rs671 were associated with a lower risk of gout in Asians [9].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also shown that genetic variations can alter the effect of alcohol intake on the aggressiveness of a range of tumors, such as prostate cancer, colon cancer [ 7 ]. For example, SNPs on the CAMK2D, ROBO1, and PRKCA genes, may increase an individual’s vulnerability to excessive alcohol intake and the development of aggressive prostate cancer [ 8 ]. And the GA and AA genotypes on rs671 were associated with a lower risk of gout in Asians [ 9 ].…”
Section: Introductionmentioning
confidence: 99%